A qualitative study of processes of change at a Swedish automobile plant. (1st January 2001) - Bildt, C.; Froberg, J.; Fredriksson, K.; Hallen, S.
In the car body-sealing department at a large automobile plant in Sweden, a reorganisation of the work from lineout to line production was performed to meet the requirement to increase production capacity and quality. A team organisation with short-cycle production targets was created to fulfil the goals, and in that process the company aimed at a broad-based participation. The new production system was planned in such a way as to lead to rotation between work tasks, increased work content and better ergonomic conditions. It appears from our results that the intended broadly based participation of the operators in the process of change was not achieved in practice, and since the full rotation of work tasks between teams was still lacking at the time of the follow-up, as was the increased work content, the disappointment among the operators was great.